БАДИИЙ – ЭТИК МАТНЛАРНИНГ БЎЛАЖАК ЎҚИТУВЧИЛАРДА КОММУНИКАТИВ-НУТҚ МАДАНИЯТЛАРИ РИВОЖЛАНИШИДАГИ ЎРНИ ВА АҲАМИЯТИ - Содиқов, Ҳ.М. (SCIENCE and SOCIETY, 2022)
The article discusses the role and importance of literary-ethical texts in the development of communicative speech culture of future teachers.
Keywords: teacher; development; idea; speech culture; activity; ethics; information; literary text; ethical text; norm; thinking